Focal Lamina Cribrosa Defect in Myopic Eyes With Nonprogressive Glaucomatous Visual Field Defect - Sawada, Yu; Araie, Makoto; Kasuga, Hitomi; Ishikawa, Makoto; Iwata, Toyoto; Murata, Katsuyuki; Yoshitomi, Takeshi (American journal of ophthalmology, 2018)
To investigate focal lamina cribrosa (LC) defect that spatially correspond to the nonprogressive glaucomatous visual field defect (VFD) in myopic subjects. Case-control study. We included 159 myopic eyes with glaucomatous VFD under treatment and followed up for 7 years. Serial enhanced-depth imaging spectral-domain optical coherence tomography B-scans of the optic discs were acquired at the end of the follow-up and reviewed for the LC defect. Nonprogressive VFD was defined as having ≤1 progressing point of Humphrey visual field, with a slope calculated using pointwise linear regression worse than −1.0 dB/year at P < .01. Eyes were classified as having either progressive or nonprogressive VFD, and associating factors were evaluated. Sixty-four subjects (40.3%) exhibited nonprogressive VFD with mean deviation change −0.06 ± 0.22 dB/year. Multivariate logistic regression analysis revealed that presence of LC defect was significantly associated with nonprogressive VFD (odds ratio, 3.96; P = .002). The location of LC defect corresponded spatially to the location of VFD. Nonprogressive eyes with LC defect exhibited lower baseline intraocular pressure (IOP) (16.6 mm Hg vs 21.0 mm Hg, P = .0030) and smaller percentage of IOP change (12.9% vs 30.5%, P < .0001) than those without LC defect, but greater myopic optic disc deformation (10.1 degrees vs 1.2 degrees in torsion angle, P < .0001). When the eyes with LC defect had higher baseline IOP, they exhibited progressive VFD. In myopic eyes, there are specific patters of LC defect that are suggested to be associated with nonprogressive glaucomatous VFD.